EVALUASI SISTEM PENGELOLAAN OBAT DI INSTALASI FARMASI RSUP Dr. KARIADI SEMARANG TAHUN 2007 - mohammad djatmiko; eni rahayu (Universitas Wahid Hasyim Semarang, 2008)
ABSTRACTDrug management in hospital sonstitutes an important aspect of hospital management. This research was inteded to find out the methods and effectiveness of drug management at Pharmaceutical Installation of Dr. Kariadi Hospital Semarang. This was non experimental research with a descriptive non analytic design. The samples were taken retrospectively from the exdisting drug supply forms, using a technique of simple random sampling, as well as from the drug prescriptions. The drug prescripsions used as the samples of data were collected by means of document reading and an interview to the head of the Drug Management Departement. The data were then translated into tables, percentages and rupiah values. The evaluations on the drug management during the period of 2007 showed that the percentage of fund availability was 95,53 %, percentage of deviation from the plans was 8,75 %, the frequency of supplying each drug type ranged 1 to 16 times per year, the congruence between the records and the drug supply forms was 100 %, the percentage of broken and expired drugs was 0,32 %, the percentage of drug dead supply was 8,57 %, the percentage of drug unavailability was 2,1 %, the percentage of served drugs was 98,97 %, the percentage of reporting timeliness was 16,67 % and the congruence between drug hospitalization forms and the drug supply forms was 100 %. Keywords : Evaluation, Drug Management, Pharmaceutical Installation of Dr. Kariadi Hospital Semarang